COVID-19 vaccine hesitancy among Mexican outpatients with rheumatic diseases - Guillermo Guaracha-Basáñez; Irazú Contreras-Yáñez; Everardo Álvarez-Hernández; Carla Marina Román-Montes; Graciela Meza-López y Olguín; María José Morales-Graciano; Salvador Saúl Valverde-Hernández; Ingris Peláez-Ballestas; Virginia Pascual-Ramos (Taylor & Francis Group, 2021)
Vaccine hesitancy (VH) has emerged as a recognized threaten to contain the COVID-19 pandemic. Historically, low vaccine acceptance rates had been described among patients with rheumatic diseases (RMDs). The study objective was to determine COVID-19 VH among Mexican outpatients with RMDs and validate the COVID-19 VH questionnaire. This cross-sectional study was developed in three steps. Step 1 consisted of translation/cultural adaptation of the Oxford-COVID-19-VH questionnaire. Step 2 consisted of pilot testing and questionnaire feasibility, content, construct and criterion validity, reliability (internal consistency and temporal stability) and questionnaire sensitivity to change. Step 3 consisted of VH phenomenon quantification in patients from two metropolitan tertiary-care-level centers. Step 1 followed ISPOR-task-force recommendations. Patients who participated in step 2 (n = 50 for pilot testing/feasibility and n = 208 for questionnaire validation [91 in test-retest and 70 in questionnaire-sensitivity to change]) and step 3 (n = 600) were representative outpatients with RMDs. The seven-item COVID-19 VH questionnaire was found feasible, valid (experts' agreement ≥80%; a 1-factor structure accounted for 60.73% of the total variance; rho = 0.156, p = .025 between COVID-19 VH questionnaire and score from the Spanish version of the Vaccine Hesitancy Scale; and lower questionnaire scores in patients who reported 5 years-previous influenza vaccination), reliable (Cronbach's ɑ = 0.889, intra-class correlation coefficient = 0.933 and 95% confidence interval = 0.898-0.956) and sensitive to change (effect size = 1.17 and 0.86, respectively, in patients who decreased [n = 34] and increased [n = 31] questionnaire-score after intervention). VH phenomenon was 35.5%. VH phenomenon was present in a substantial number of Mexican patients with RMDs. The COVID-19 VH questionnaire showed good psychometric properties to assess COVID-19 VH in our population.